2010
DOI: 10.1136/oem.2009.049874
|View full text |Cite
|
Sign up to set email alerts
|

The effects of timing on the cost-effectiveness of interventions for workers on sick leave due to low back pain

Abstract: With a good RTW in the first weeks, the only early interventions likely to be cost-beneficial are inexpensive work-focused enhancements to early routine care, such as accommodating workplaces. Structured interventions are unlikely to have an additional impact on the already good prognosis when offered before the optimal time window at approximately 8 to 12 weeks. The generalisibility of the effectiveness of a RTW intervention depends on the comparability of baseline characteristics and RTW curves in tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
0
32
1
1
Order By: Relevance
“…This timeframe is very similar to the timing used in the present study (most participants were included at between 8-10 weeks of sickness absence benefits). However, it should be recognized that the RTW recovery rate in the present study was far lower than the recovery rate characterized as slow in the study on RTW and lowback pain (21).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This timeframe is very similar to the timing used in the present study (most participants were included at between 8-10 weeks of sickness absence benefits). However, it should be recognized that the RTW recovery rate in the present study was far lower than the recovery rate characterized as slow in the study on RTW and lowback pain (21).…”
Section: Discussioncontrasting
confidence: 74%
“…However, at later stages of the absence spells, when only more complex cases are under consideration (under the assumption that the most straightforward cases have been solved and closed), the effect of the CTM intervention might become superior to OSM, leading to a statistically significant HR for spells that lasted >42 weeks in M1. It has been recently demonstrated that timing is crucial for the cost-effectiveness of structured and complex interventions for workers on sick leave due to low-back pain (21). Using theoretical modeling, the authors estimated the optimal time window to be between 8-12 weeks for a population with a slow RTW (RTW of 43% after 2 weeks and 79% after 12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the effectiveness of return to work (RTW) interventions after injury and illness (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These have ranged from minimal postal intervention, OH phone intervention to multidisciplinary approaches involving workplace assessment, work modifications and importantly case management involving all stakeholders (22)(23)(24)(25).…”
Section: Brown Et Almentioning
confidence: 99%
“…The effects were in general modest: mean reduction in sickness absence being only 1.1 days per month -and even lower in higher quality studies -and similar between the different types of interventions. Van Duijn et al (8) looked at the effects of different timing of structured interventions on RTW. They modeled gained sickness absence days with differently timed interventions among populations with expected fast or slow RTW.…”
Section: Viikari-juntura Et Almentioning
confidence: 99%
“…However, recent systematic reviews (7) and economic analyses (8) have emphasized that few have proven to be cost-effective. It has been difficult to find costeffective solutions for RTW especially at the early stage of disability.…”
Section: Control Group Intervention Groupmentioning
confidence: 99%